2013
DOI: 10.3354/meps10517
|View full text |Cite
|
Sign up to set email alerts
|

Elevated ammonium concentrations and low light form a dangerous synergy for eelgrass Zostera marina

Abstract: We studied the effect of ecologically relevant ammonium concentrations and light on several morphological and physiological properties, nitrogen metabolism and carbon reserves of eelgrass Zostera marina L. Eelgrass was grown under mesocosm conditions at 3 levels of ammonium enrichment (target concentrations of 0, 10 and 25 µM) and 2 levels of light (low and high light). High ammonium supply combined with low light had a negative effect on several morphological and physiological response parameters, while no su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 61 publications
(70 reference statements)
5
31
0
Order By: Relevance
“…The amount of glutamate (major product of assimilation and source for most amino acids) and glutamine (major N reserve in plants) decreased, in contrast, and the authors concluded that eelgrass slows down N uptake and assimilation when light is insufficient. The N content in plants from our LL + HN treatment increased however from 2.5% to 3.5% of DW over the course of the experiment, which corresponds the response observed by Villazán et al () who also showed that the increase in N largely could be explained from accumulation of amino acids. We cannot explain why our findings disagree with those of Hasler‐Sheetal et al (), but their plants contained very high levels of N (ca.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…The amount of glutamate (major product of assimilation and source for most amino acids) and glutamine (major N reserve in plants) decreased, in contrast, and the authors concluded that eelgrass slows down N uptake and assimilation when light is insufficient. The N content in plants from our LL + HN treatment increased however from 2.5% to 3.5% of DW over the course of the experiment, which corresponds the response observed by Villazán et al () who also showed that the increase in N largely could be explained from accumulation of amino acids. We cannot explain why our findings disagree with those of Hasler‐Sheetal et al (), but their plants contained very high levels of N (ca.…”
Section: Discussionsupporting
confidence: 91%
“…c,d), which may seem strange if the metabolism of organic N‐compounds was limited by LL. However, Villazán et al () found a similar pattern and showed that the increase in total N in shade plants covered over a drop in amino acids and proteins while the content of NH4+, NO3, and unidentified N‐compounds increased dramatically.…”
Section: Discussionmentioning
confidence: 79%
See 3 more Smart Citations